2016
DOI: 10.1007/s00467-016-3335-3
|View full text |Cite
|
Sign up to set email alerts
|

Underlying genetic factors of the VATER/VACTERL association with special emphasis on the “Renal” phenotype

Abstract: The acronym VATER/VACTERL association (OMIM #192350) refers to the rare non-random co-occurrence of the following component features (CFs): vertebral defects (V), anorectal malformations (A), cardiac defects (C), tracheoesophageal fistula with or without esophageal atresia (TE), renal malformations (R), and limb defects (L). According to epidemiological studies, the majority of patients with VATER/VACTERL association present with a “Renal” phenotype comprising a large spectrum of congenital renal anomalies. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 63 publications
3
31
0
Order By: Relevance
“…There is a known association of CAKUT with VACTERL(-like) phenotypes and numerous monogenic syndromes can clinically present as VACTERL (eg, Townes-Brocks syndrome or Baller Gerold syndrome). 60 VACTERL is a term describing the nonrandom co-occurrence of several congenital anomalies and involves heterogeneous causes that can be both multifactorial and monogenic. Therefore, diagnostic yield from cohorts with phenotypes including VACTERL characteristics is low (14% in one publication).…”
Section: Discussionmentioning
confidence: 99%
“…There is a known association of CAKUT with VACTERL(-like) phenotypes and numerous monogenic syndromes can clinically present as VACTERL (eg, Townes-Brocks syndrome or Baller Gerold syndrome). 60 VACTERL is a term describing the nonrandom co-occurrence of several congenital anomalies and involves heterogeneous causes that can be both multifactorial and monogenic. Therefore, diagnostic yield from cohorts with phenotypes including VACTERL characteristics is low (14% in one publication).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the VACTERL association phenotype describes a combination of congenital malformations, it is logical that abnormalities in the genes involved in regulating development as well as those moderating the complex network of signaling pathways––such as Sonic hedgehog (SHH), may be the culprits (Kim, Kim, & Hui, ). Research in determining its genetic etiology has focused on previously identified candidate genes, namely, FGF8, FOXF1, HOXD13, LPP, TRAP1 and ZIC3 (Reutter, Hilger, Hildebrandt, & Ludwig, ). Additionally in an effort to identify the genetic cause of VACTERL association, Shi et al () performed genomic sequencing in families and identified pathogenic variants in gene encoding enzymes of the kynurenine pathway, namely 3‐hydroxyanthranilic acid 3, 4‐dioxygenase (HAAO) and kynureninase (KYNU), resulting in disruption of de novo synthesis and deficiency of nicotinamide adenine dinucleotide (NAD) – a vital co‐factor for embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a large study of patients diagnosed with VACTERL association, 80% exhibited kidney defects and 48% exhibited cardiac defects ( 23 ). In humans, several genes have been related to VACTERL association including FGF8, FOXF1, HOXD13, LPP, TRAP1, and ZIC3 , all of which have been implicated in kidney developmental anomalies, with ZIC3 being an X-linked gene also shown to cause heterotaxy ( 24 ).…”
Section: Association Of Heart and Kidney Phenotypes In Genetic Syndromentioning
confidence: 99%